Effects of irrigation level and method on soil salt balance and crop water use efficiency in arid oasis regions - Tang, Liping; Shi, Xueshuang; Song, Zhipeng; Zhao, Han; Li, Fahu (International Journal of Agricultural and Biological Engineering, 2024)
Fresh water resource scarcity and soil salt accumulation in the root-zone are two key limiting factors for sustainable agricultural development in the oasis region of arid inland basin, northwest China. The aim of this study was to explore an appropriate irrigation scheme to maintain sustainable crop cultivation in this region. The effects of four irrigation levels (full irrigation, mild deficit, moderate deficit, and severe deficit) and three irrigation methods (border, surface drip and subsurface drip) on soil water and salt dynamics, highland barley (Hordeum vulgare L.) yield, and crop water use efficiency were studied by field plot experiments. The results showed that soil salt in 0-100 cm profile was accumulated under all experimental treatments after one season of highland barley planting, but the accumulated salt mass decreased with the decrease of the lower limit of irrigation. Salt mass in 0-100 cm soil profile under subsurface drip irrigation was 16.8%-57.8% and 2.9%-58.4% less than that under border and surface drip irrigation, respectively. The grain yield of highland barley decreased first and then increased with the decrease of the lower limit of irrigation under surface drip and subsurface drip irrigation, but it was on the contrary under border irrigation. Mean grain yield for all irrigation levels under subsurface drip irrigation was 5.7% and 18.8% higher than that under border and surface drip irrigation, respectively. Water use efficiency increased with the decrease of the lower limit of irrigation, and the averaged water use efficiency of all irrigation levels under subsurface drip irrigation was 11.9% and 14.2% higher than that under border and surface drip irrigation, respectively. Considering economic benefit and irrigation water requirement, subsurface drip irrigation with the lower limit of irrigation of 50%-55% field capacity is suggested for highland barley planting in the arid oasis region. Keywords: arid oasis, highland barley, irrigation method, irrigation level, soil salt balance, water use efficiencyDOI: 10.25165/j.ijabe.20231606.7788Citation: Tang L P, Shi X S, Song Z P, Zhao H, Li F H. Effects of irrigation level and method on soil salt balance and cropwater use efficiency in arid oasis regions. Int J Agric & Biol Eng, 2023; 16(6): 158–166.